The Effect of Unconventional Fertilizers on the Growth and Development of Cotton - Ismailova Aksungul Uzakbaevna (Researchparks Publishing, 2022)
In order to study the effect of unconventional fertilizers (glauconite, glaucophos) on the growth and development of cotton in the saline soils of the Republic of Karakalpakstan, field experiments were conducted. As a result of the received information using unconventional fertilizers together with mineral fertilizers in feeding cotton is efficient in economic and ecological sides. At the same time, by reducing the annual norm of mineral fertilizers by 25% and replacing them with unconventional fertilizers, it will be possible to reduce the amount of mineral fertilizers in the soil, while fully satisfying the demand of cotton for micronutrients. Feeding of unconventional fertilizers in the amount of 1200 kg / ha, including 600 kg / ha under plowing, 600 kg / ha during the growing season, application of mineral fertilizers in the amount of N190 P130 K90 kg / ha has been found to have a positive effect on good growth and development of cotton.